2023
DOI: 10.3390/ma16062305
|View full text |Cite
|
Sign up to set email alerts
|

Modification Effect of Ca(OH)2 on the Carbonation Resistance of Fly Ash-Metakaolin-Based Geopolymer

Abstract: Compared with Portland cement, geopolymers have poor carbonization resistance, which will greatly limit the application their application. To improve the carbonization resistance of geopolymers, firstly, the carbonization behavior of the fly ash-metakaolin-based geopolymer was studied through accelerated carbonization tests. Secondly, different amounts of Ca(OH)2 were introduced into the composite system, and the modification effect of the carbonization resistance of the modified geopolymer was studied. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…From the perspective of participating in the reaction, the FGD itself participated in the reaction of the cementitious system, generating ettringite crystals. In addition, from the perspective of activity excitation, the addition of FGD provided SO 4 2− , which can also change the S/C of C-S-H and promote the conversion of C-S-H with a high silica/calcium ratio to gel with a low silica/calcium ratio [32,33].…”
Section: Analysis On the Strength Mechanism Of Swcm 321 Xrd Analysis ...mentioning
confidence: 99%
“…From the perspective of participating in the reaction, the FGD itself participated in the reaction of the cementitious system, generating ettringite crystals. In addition, from the perspective of activity excitation, the addition of FGD provided SO 4 2− , which can also change the S/C of C-S-H and promote the conversion of C-S-H with a high silica/calcium ratio to gel with a low silica/calcium ratio [32,33].…”
Section: Analysis On the Strength Mechanism Of Swcm 321 Xrd Analysis ...mentioning
confidence: 99%
“…Kim et al [7] also observed that the addition of Ca(OH) 2 resulted in superior mechanical properties in metakaolin-based geopolymers. Lv et al [24] observed that the addition of Ca(OH) 2 to fly ash and metakaolin-based geopolymers can significantly improve the compressive strength.…”
Section: Introductionmentioning
confidence: 99%